The Biodiversity of Gastropods In Karapyak Rocky Shores, Pangandaran Region, West Java Province, Indonesia - Asep Sahidin; Zahidah Zahidah; Herman Hamdani; Indah Riyantini; Roni Sewiko (Fisheries and Marine Science Faculty - Jenderal Soedirman University)
Pangandaran rocky shores have a unique ecosystem and a variant of invertebrate organisms such as mollusk from the gastropod class. This study aims to analyze the biodiversity of gastropods on the rocky shore of Karapyak beach. This research consists of 5 stations. The quadrant set by 1 m x 1 m vertically toward the sea. The result found 773 individuals scattered in nine families. The family of Neritidae dominated (43%), followed by family cyprinoids with 6.3%. Nerita plicata is a species found to dominate in every station with an average abundance (256 ± 10) and/m2. Using the Bray-Curtis cluster analysis, showed variations in the distribution and abundance of different gastropods vertically into the ocean and uniformly distributed horizontally to the shore. Substrate and tidal are the main variables in the spatial distribution of gastropods in the Karapyak beach.